Magnetically induced elastic deformations in model systems of magnetic gels and elastomers containing particles of mixed size. (1st December 2020) - Fischer, Lukas; Menzel, Andreas M
Abstract: Soft elastic composite materials can serve as actuators when they transform changes in external fields into mechanical deformation. Here, we theoretically address the corresponding deformational behavior in model systems of magnetic gels and elastomers exposed to external magnetic fields. In reality, such materials consist of magnetizable colloidal particles in a soft polymeric matrix. Since many practical realizations of such materials involve particulate inclusions of polydisperse size distributions, we concentrate on the effect that mixed particle sizes have on the overall deformational response. To perform a systematic study, our focus is on binary size distributions. We systematically vary the fraction of larger particles relative to smaller ones and characterize the resulting magnetostrictive behavior. The consequences for systems of various different spatial particle arrangements and different degrees of compressibility of the elastic matrix are evaluated. In parts, we observe a qualitative change in the overall response for selected systems of mixed particle sizes. Specifically, overall changes in volume and relative elongations or contractions in response to an induced magnetization can be reversed into the opposite types of behavior. Our results should apply to the characteristics of other soft elastic composite materials like electrorheological gels and elastomers when exposed to external electric fields as well. Overall, we hope to stimulate corresponding experimental realizations and the further investigation on the purposeful use of mixed particle sizes as a means to design tailored requested material behavior.